2021
DOI: 10.3390/ijms22116019
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Phenotype in Polycystic Kidney Disease Is Determined by Differential Intracellular Ca2+ Signals

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is caused by loss of function of PKD1 (polycystin 1) or PKD2 (polycystin 2). The Ca2+-activated Cl− channel TMEM16A has a central role in ADPKD. Expression and function of TMEM16A is upregulated in ADPKD which causes enhanced intracellular Ca2+ signaling, cell proliferation, and ion secretion. We analyzed kidneys from Pkd1 knockout mice and found a more pronounced phenotype in males compared to females, despite similar levels of expression for renal tubular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…It was reported that PKD is more severe in males than in female PCK rats (Lager et al, 2001). Moreover, intracellular Ca 2+ signaling and ATP‐induced response are enhanced in male epithelial cells, further driving cell proliferation and cyst growth (Talbi et al, 2021). Thus in our case, the potential difference in treatment between males in females is doubtful, and we did not explore it in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PKD is more severe in males than in female PCK rats (Lager et al, 2001). Moreover, intracellular Ca 2+ signaling and ATP‐induced response are enhanced in male epithelial cells, further driving cell proliferation and cyst growth (Talbi et al, 2021). Thus in our case, the potential difference in treatment between males in females is doubtful, and we did not explore it in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although sex bias in the severity and progression of the disease is expected for the two Col4a5 models due to their X-linked nature, such bias is not expected for the autosomal Co4a3- and Co4a4 -based models. However, the phenotype of another autosomal kidney disease, polycystic kidney disease, is presented in a sex-dependent manner, despite its autosomal nature [ 34 ]. In addition, sex and background-dependent differences in the composition of GBM, associated with albuminuria, are reported in healthy mice [ 31 ].…”
Section: Comparison Of Sex Morphological and Physiological Characteri...mentioning
confidence: 99%
“…Interestingly, gender-dependent differences were recently observed in intracellular Ca 2+ concentration ([Ca 2+ ] i ) in ADPKD epithelium. Specifically, higher basal and ATP-induced [Ca 2+ ] i levels were detected in primary renal epithelial cells isolated from male mice (vs female cells), which were hypothesized to result in the larger TMEM16A currents in males [ 126 ].…”
Section: Regulation Of Calcium Handling In Pkd: Polycystins Cilia Calcium Channels Transporters and Purinergic Signaling-dependent Calciumentioning
confidence: 99%